Preparation method of antibacterial anti-mite healthy cotton fiber based on compounding of copper-silver alloy and graphene fiber
Through technical means such as pomegranate-like structure Cu-Ag alloy, copper-silver core-shell nanoparticles and modified copper antibacterial agents, healthy cotton fibers with excellent antibacterial and mite properties were successfully prepared, and the materials were solved Combined with the problems, the needs of a healthy life are met.
Patent Information
- Application Number
- CN202411252710.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-17
AI Technical Summary
How to effectively combine graphene fiber, copper-silver alloy and cotton fiber in composite materials to maintain their excellent performance and solve the problem of material bonding in the preparation process of antibacterial and mite-resistant textiles.
The combination of graphene/carbon nanofiber composite material and cotton fibers is prepared through a multi-step process using pomegranate-like structure Cu-Ag alloy, copper-silver core-shell bimetal nanoparticles, modified copper antibacterial agent and nano-anti-mite antibacterial finishing agent. Form antibacterial and anti-mites healthy cotton fibers.
It has achieved significant improvement in antibacterial and mite-proof performance, while retaining the comfort and breathability of cotton fibers. It is suitable for bedding, clothing and medical supplies, etc., to meet the needs of healthy living.
Smart Images

Figure CN119145213A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a new material, and in particular to a method for preparing antibacterial and anti-mite healthy cotton fiber based on a composite of copper-silver alloy and graphene fiber. Background Art
[0002] Graphene fiber has excellent mechanical properties, electrical conductivity, thermal conductivity and chemical stability, providing a strong physical and chemical basis for composite materials. Copper-silver alloy combines the excellent properties of copper and silver, especially the antibacterial property of silver ions, which can significantly enhance the antibacterial properties of composite materials.
[0003] As people's requirements for health and quality of life continue to increase, the market demand for antibacterial and anti-mite textiles is growing. Antibacterial and anti-mite healthy cotton fiber based on copper-silver alloy and graphene fiber composite not only has excellent antibacterial and anti-mite properties, but also retains the comfort and breathability of cotton fiber. It will be widely used in home, medical, sports and other fields. In the preparation process of composite fiber, how to effectively combine graphene fiber, copper-silver alloy and cotton fiber while maintaining their respective excellent properties is a technical problem. Summary of the invention
[0004] In view of the above problems, the present invention provides an antibacterial and anti-mite healthy cotton fiber based on a composite of copper-silver alloy and graphene fiber.
[0005] The present invention provides a method for preparing an antibacterial and anti-mite healthy cotton fiber based on a composite of a copper-silver alloy and graphene fiber, comprising the following steps: synthesis of a pomegranate-shaped structured Cu-Ag alloy, preparation of copper-silver core-shell bimetallic nanoparticles, copper-silver bimetallic core-shell nanoparticle materials, surface modification of a copper antibacterial agent, preparation of a nano anti-mite and antibacterial finishing agent, preparation of a graphene / carbon nanofiber composite material, and preparation of an antibacterial and anti-mite healthy cotton fiber.
[0006] Preferably, step (1) synthesis of pomegranate-shaped Cu-Ag alloy
[0007] A soluble copper salt, polyvinyl pyrrolidone and a soluble silver salt are added to a solvent diethylene glycol to obtain a copper salt solution, a polyvinyl pyrrolidone solution and a silver salt solution; the polyvinyl pyrrolidone solution is added dropwise to the copper salt solution, and a reduction reaction is continuously performed under stirring to obtain a Cu suspension; the polyvinyl pyrrolidone solution and the silver salt solution are simultaneously added dropwise to the Cu suspension, and a reduction reaction is continuously performed under stirring to obtain a Cu-Ag suspension; the Cu-Ag suspension is centrifuged, washed and dried in sequence to obtain a pomegranate-shaped structure Cu-Ag alloy;
[0008] Step (2) Preparation of copper-silver core-shell bimetallic nanoparticles
[0009] The pomegranate-shaped Cu-Ag alloy, PVP and ethanol prepared in step (1) are poured into a three-necked flask 1, and stirred to dissolve after heating; ascorbic acid is poured into a three-necked flask 2, and then ethanol is poured into the three-necked flask, and stirred to dissolve after heating; the three-necked flask 1 is kept heated and stirred, and the solution in the three-necked flask 2 is poured into the three-necked flask 1, and the heating and stirring reaction is continued; after the reaction is completed, the heating is stopped and the temperature is cooled to room temperature, after adding deionized water to break the stability, the solution is centrifuged to make the nano copper particles settle, and the supernatant is poured out, and deionized water is added, ultrasonic dispersion is performed, and the nano copper particles are fully washed in deionized water, and the supernatant is poured out by centrifugation, and the washing is repeated, and anhydrous ethanol is added, ultrasonic dispersion is performed, and the nano copper particles are fully washed in anhydrous ethanol, and the supernatant is poured out by centrifugation, and the washing is repeated, and finally the collected nano particles are placed in a vacuum drying oven, and dried at room temperature under vacuum conditions to obtain a copper-silver core-shell bimetallic nanoparticle material;
[0010] Step (3) Copper-silver bimetallic core-shell nanoparticle material
[0011] After the copper-silver core-shell bimetallic nanoparticles prepared in step (2) are fully ground and dispersed, the nano-copper particles are poured into a three-necked flask, and then poured into deionized water. The three-necked flask is placed in an ultrasonic cleaner and ultrasonically dispersed in the nano-copper particles at room temperature, while mechanically stirring. The ultrasonic dispersion and mechanical stirring are maintained at room temperature, and a dilute nitric acid solution is poured into the three-necked flask. After the reaction, a sodium hydroxide solution is poured to neutralize the nitric acid, thereby completing the pretreatment of the nano-copper. The ultrasonic dispersion and mechanical stirring are maintained at room temperature, and a solvent, a solution containing silver nitrate, are poured into the three-necked flask. deionized water, ammonia and gelatin coating solution, and the silver shell coating is completed after the reaction; after the reaction is completed, the solution is taken out, centrifuged to settle the particles, and then the supernatant is poured out, and deionized water is added, ultrasonic dispersion is performed, so that the nano copper particles are fully washed in deionized water, and then centrifuged to pour out the supernatant, and the washing is repeated, and anhydrous ethanol is added, ultrasonic dispersion is performed, so that the nano copper particles are fully washed in anhydrous ethanol, and then centrifuged to pour out the supernatant, and the collected particles are placed in a vacuum drying oven and dried at room temperature under vacuum conditions;
[0012] Step (4) Surface modification of copper antimicrobial agent
[0013] The antibacterial drug is dissolved, and then di-tert-butyl dicarbonate is added to react under an inert gas atmosphere to obtain a Boc (tert-butyloxycarbonyl) protected antibacterial drug; the Boc protected antibacterial drug, N,N-dimethylaminoethyl glycol, TBTU (tetrafluoroborate) and DIPEA (N,N-diisopropylethylamine) are mixed and added to a solvent, and stirred at room temperature to react to obtain a mixed product; the mixed product is dissolved, and then tert-butyl bromoacetate and a base are added to react under an inert gas atmosphere to obtain an antibacterial mixture; the mixture is subjected to a de-tert-butyl esterification reaction in a mixed solvent of dichloromethane and trifluoroacetic acid, and then precipitated and filtered to obtain an antibacterial agent; under the protection of a nitrogen atmosphere, glacial acetic acid and oleic acid are sequentially added to an anhydrous ethanol solution, and after the reflux reaction is completed, the solution is washed and filtered with anhydrous ethanol and ultrapure water in sequence, and freeze-dried to obtain a modified copper antibacterial agent;
[0014] Step (5) Preparation of nano anti-mite and antibacterial finishing agent
[0015] Weigh nano-TiO2 powder, Ag dispersion medium (anhydrous ethanol), dispersant OP, citric acid, and the modified copper antibacterial agent prepared in step (4), and stir. The obtained emulsion is very stable and only a small amount of precipitation is left after standing. A nano anti-mite antibacterial finishing agent is prepared.
[0016] Step (6) Preparation of graphene / carbon nanofiber composite material
[0017] First, graphene oxide is dissolved in DMF, the temperature is set to a certain value, and the frequency of ultrasound is adjusted for a period of time to obtain a dispersed suspension; then PAN is added to the above suspension, the mass content of graphene oxide in the suspension is a certain value, the nano anti-mite and antibacterial finishing agent prepared in step (5) is added, and the above suspension is placed in a constant temperature water bath with the temperature set to a certain value, and vigorously stirred to finally obtain the required electrospinning solution, and the copper-silver bimetallic core-shell nanoparticle material prepared in step (3) is added to prepare the precursor of the composite fiber membrane, and then placed in a drying oven and pre-oxidized in an air atmosphere to stabilize the composite fiber precursor, and finally the pre-oxidized composite fiber membrane is placed in a tubular furnace and carbonized in a nitrogen atmosphere, and the tubular furnace is heated and then kept warm to obtain a graphene / carbon nanofiber composite material;
[0018] Step (7) Preparation of antibacterial and anti-mite healthy cotton fiber
[0019] After the graphene / carbon nanofiber composite material prepared in step (6) is scour-bleached, the prepared cotton fiber is placed in a sodium periodate solution and then oscillated in the absence of light. After the oxidation is completed, the cotton fiber is immersed in a propylene glycol solution to remove the remaining unreacted oxidant. Finally, the cotton fiber is thoroughly washed with distilled water and dried to obtain an antibacterial and anti-mite healthy cotton fiber.
[0020] Preferably, step (1) synthesis of pomegranate-shaped Cu-Ag alloy
[0021] At a temperature of 75-85°C, a soluble copper salt, polyvinyl pyrrolidone and a soluble silver salt are added to a solvent diethylene glycol to obtain a copper salt solution, a polyvinyl pyrrolidone solution and a silver salt solution; the polyvinyl pyrrolidone solution is added dropwise to the copper salt solution, and a reduction reaction is continued for 1-2 hours at a temperature of 180-220°C and under stirring to obtain a Cu suspension; the polyvinyl pyrrolidone solution and the silver salt solution are simultaneously added dropwise to the Cu suspension, and a reduction reaction is continued for 1.5-2 hours at a temperature of 75-85°C and under stirring to obtain a Cu-Ag suspension; the Cu-Ag suspension is centrifuged, washed and dried in sequence to obtain a pomegranate-shaped structure Cu-Ag alloy.
[0022] The invention has the advantage that the Cu-Ag alloy exists in a pomegranate-like structure, which is conducive to increasing the specific surface area of the alloy and improving the surface activity of the material, thereby enhancing its antibacterial and anti-mite properties. Ag and Cu elements are evenly distributed in the alloy, which helps to achieve a wider antibacterial coverage and reduce dead corners.
[0023] Among them, Cu and Ag are both elements with excellent antibacterial properties. Their combined use can further enhance the antibacterial effect of the alloy; by combining the pomegranate-shaped structured Cu-Ag alloy with graphene fiber, healthy cotton fibers with excellent antibacterial and anti-mite properties can be prepared. This fiber is suitable for making various bedding, clothing, medical supplies, etc., to meet people's needs for healthy living.
[0024] Preferably, step (2) preparation of copper-silver core-shell bimetallic nanoparticles
[0025] Pour 1-5g of the pomegranate-shaped Cu-Ag alloy prepared in step (1), 5-12g of PVP and 95-100ml of ethanol into three-necked flask 1, heat to 60-65°C and stir to dissolve; Pour 15-20g of ascorbic acid into three-necked flask 2, then pour 455-500ml of ethanol, heat to 65-70°C and stir to dissolve; Keep heating and stirring the three-necked flask 1, pour the solution in the three-necked flask 2 into the three-necked flask 1, continue heating and stirring to react for 5-10min; After the reaction is completed, stop heating and cool to room temperature, add deionized water to break the stability, and centrifuge Centrifuge at 9500-10000r / min for 1-5min to allow the nano-copper particles to settle, then pour out the supernatant, add deionized water, ultrasonically disperse, fully wash the nano-copper particles in deionized water, centrifuge and pour out the supernatant, repeat the washing 1-3 times, add anhydrous ethanol, ultrasonically disperse to fully wash the nano-copper particles in anhydrous ethanol, centrifuge and pour out the supernatant, repeat the washing 1-3 times, finally place the collected nanoparticles in a vacuum drying oven, dry at room temperature under -1-1MPa vacuum conditions for 1-4h to obtain a copper-silver core-shell bimetallic nanoparticle material.
[0026] The present invention has the advantages that anhydrous ethanol and deionized water are used for multiple washings during the preparation process, which effectively removes impurities and unreacted raw materials and improves the purity of the nanoparticles. At the same time, through ultrasonic dispersion, the nanoparticles are fully dispersed in the deionized water and anhydrous ethanol, avoiding agglomeration between particles and improving the dispersibility of the nanoparticles.
[0027] The copper-silver core-shell bimetallic nanoparticles have a stable core-shell structure, which not only combines the excellent properties of copper and silver, such as the electrical conductivity of copper and the antibacterial property of silver, but also enhances the stability and durability of the nanoparticles through the core-shell structure;
[0028] Due to the presence of the silver shell, the copper-silver core-shell bimetallic nanoparticles have excellent antibacterial properties. Silver ions can destroy the cell membrane and DNA of bacteria, thereby effectively inhibiting the growth and reproduction of bacteria. This antibacterial property makes the material have broad application prospects in the fields of medicine, hygiene, and textiles.
[0029] Preferably, in step (3), the copper-silver bimetallic core-shell nanoparticle material
[0030] After the copper-silver core-shell bimetallic nanoparticles prepared in step (2) are fully ground and dispersed, 0.2-0.5 g of nano-copper particles are weighed and poured into a three-necked flask, and then 15-20 ml of deionized water is poured into the flask. The three-necked flask is placed in an ultrasonic cleaner to ultrasonically disperse the nano-copper particles at room temperature, while mechanically stirring; while maintaining the ultrasonic dispersion and mechanical stirring at room temperature, 25-30 ml of 0.1-0.5 mol / L dilute nitric acid solution is poured into the three-necked flask, reacted for 25-30 seconds, and then 45-50 ml of 0.02-0.05mol / L sodium hydroxide solution is used to neutralize nitric acid to complete the pretreatment of nano copper; ultrasonic dispersion and mechanical stirring are maintained at room temperature, and 95-100ml of solvent, deionized water containing 0.001-0.005mol silver nitrate, 0.004-0.008mol ammonia water and 1-2g of gelatin coating solution are poured into a three-necked flask, and the reaction is carried out for 1-5min to complete the silver shell coating; after the reaction is completed, the solution is taken out and centrifuged at 9500 Centrifuge at -10000r / min for 1-5min to allow the particles to settle, then pour out the supernatant, add deionized water, and disperse by ultrasound to fully wash the nano-copper particles in deionized water, then centrifuge and pour out the supernatant, repeat the washing 1-4 times, add anhydrous ethanol, and disperse by ultrasound to fully wash the nano-copper particles in anhydrous ethanol, then centrifuge and pour out the supernatant, place the collected particles in a vacuum drying oven, and dry at room temperature under a vacuum condition of -1-1MPa.
[0031] The present invention has the advantages that the nano copper particles are firstly fully treated by ultrasonic dispersion and mechanical stirring, thereby ensuring uniform dispersion of the nano particles and providing a good foundation for subsequent silver shell coating.
[0032] Through precise control of dilute nitric acid and sodium hydroxide solutions, the nano-copper particles were effectively pre-treated to remove surface oxides and other impurities, improve the purity and surface activity of the nano-particles, and facilitate the subsequent uniform coating of the silver shell. In addition, through the alternating use of deionized water and anhydrous ethanol, excess coating liquid and impurities were effectively removed, ensuring the purity and dispersibility of the nano-particles.
[0033] Preferably, in step (4), surface modification of the copper antibacterial agent
[0034] The antibiotic is dissolved, and then di-tert-butyl dicarbonate is added to react under an inert gas atmosphere to obtain a Boc (tert-butyloxycarbonyl) protected antibiotic; the Boc protected antibiotic, N,N-dimethylaminoethyl glycol, TBTU (tetrafluoroborate) and DIPEA (N,N-diisopropylethylamine) are mixed in a molar ratio of 1--2:2-4:3-5:6-8 and added to a solvent, and the mixture is stirred for reaction at room temperature for 10-15 hours to obtain a mixed product; the mixed product is dissolved, and then tert-butyl bromoacetate and a base are added at 45-55 ℃, react for 0.5-1.5h in an inert gas atmosphere to obtain an antibacterial mixture; carry out de-tert-butyl esterification reaction of the mixture in a mixed solvent of dichloromethane and trifluoroacetic acid, and then precipitate and filter to obtain an antibacterial agent; under the protection of a nitrogen atmosphere, 15-20g of a copper antibacterial agent, 1-5mL of glacial acetic acid and 1-5mL of oleic acid are successively added to 350-400mL of anhydrous ethanol solution, and refluxed at 75-80℃ for 5-8h. After the reaction is completed, it is washed and filtered with anhydrous ethanol and ultrapure water in succession, and freeze-dried for 20-26h to obtain a modified copper antibacterial agent.
[0035] The advantage of the present invention is that, by introducing organic molecules such as glacial acetic acid and oleic acid on the surface of the copper antibacterial agent, its surface properties can be improved, thereby enhancing its antibacterial effect; these organic molecules help to increase the release rate of copper ions on the surface or improve their interaction with bacterial cell membranes, thereby more effectively killing or inhibiting the growth of bacteria, which is beneficial to improving the stability of the modified copper antibacterial agent in the environment.
[0036] Preferably, step (5) preparation of nano anti-mite and antibacterial finishing agent
[0037] Weigh 15-20 g of nano-TiO2 powder, 15-20 g of Ag, 95-100 ml of dispersant OP, 15-30 g of citric acid, and 55-60 g of citric acid. Add the modified copper antibacterial agent prepared in step (4), pH 1-7, stirring time 25-30 min, stirring speed 5550-6000 r / min. The obtained emulsion is very stable and only a small amount of precipitation is obtained after standing. Nano anti-mite antibacterial finishing agent is prepared.
[0038] The invention has the advantages that the finishing agent combines the antibacterial properties of nano-TiO2 and Ag, and the antibacterial effect of the modified copper antibacterial agent, forming a multiple antibacterial and anti-mite mechanism; nano-TiO2 can produce a photocatalytic effect under light conditions, decompose organic matter and kill bacteria; Ag ions have a broad-spectrum antibacterial property and can effectively inhibit the growth of a variety of bacteria; and the modified copper antibacterial agent enhances the antibacterial effect by releasing copper ions;
[0039] By selecting appropriate dispersion medium (anhydrous ethanol) and dispersant (OP), as well as controlling stirring time and speed, the obtained emulsion is very stable, which indicates that the nanoparticles in the finishing agent are effectively dispersed and stabilized, avoiding particle agglomeration and sedimentation; the raw materials used, such as nano-TiO2, Ag and modified copper antibacterial agents, are all environmentally friendly materials, and the entire preparation process is carried out under relatively mild conditions without producing toxic and harmful substances.
[0040] Preferably, step (6) preparation of graphene / carbon nanofiber composite material
[0041] First, 0-0.12g of graphene oxide is dissolved in 15-17g of DMF, and the temperature is set to 25-30°C, the power is set to 95-100W, and the frequency is set to 40-45Hz for 25-30min to obtain a dispersed suspension; then 1-3g of PAN is added to the above suspension, and the mass content of graphene oxide in the suspension is 0-4%; the nano anti-mite and antibacterial finishing agent prepared in step (5) is placed in a constant temperature water bath set at 55-60°C and stirred vigorously. 12-24h, finally obtaining the required electrospinning solution, preparing the precursor of the composite fiber membrane by the copper-silver bimetallic core-shell nanoparticle material prepared in step (3), and then placing it in a drying oven, and performing a pre-oxidation treatment in an air atmosphere to stabilize the composite fiber precursor, and finally placing the pre-oxidized composite fiber membrane in a tubular furnace for carbonization treatment in a nitrogen atmosphere, the tubular furnace heating rate is 1-5°C / min, the temperature is raised to 800-1100°C, and then kept warm for 5-10min; obtaining a graphene / carbon nanofiber composite material.
[0042] The present invention has the advantage that, by dissolving graphene oxide in DMF, the uniform dispersion of graphene oxide in the solvent can be ensured, and this uniform dispersion is the basis for preparing high-quality composite materials, helps to avoid agglomeration, and improves the overall performance of the composite materials;
[0043] Among them, adding PAN to the suspension and stirring it vigorously for a period of time can form a stable spinning solution. The stability of this spinning solution can ensure the smooth progress of the subsequent electrospinning process and reduce problems such as wire breakage during the spinning process.
[0044] As a preferred method, step (7) preparation of antibacterial and anti-mite healthy cotton fiber
[0045] After the graphene / carbon nanofiber composite material prepared in step (6) is scourged and bleached, the prepared cotton fiber is placed in a sodium periodate solution with a concentration of 0.5-30 g / L, and then oscillated at 35-40 r / min for 1-5 hours at 40-45°C in the absence of light. After the oxidation is completed, the cotton fiber is immersed in a 0.1-0.4 mol / L propylene glycol solution for 25-30 hours to remove the remaining unreacted oxidant, and finally thoroughly washed with distilled water and dried to obtain antibacterial and anti-mite healthy cotton fiber.
[0046] The invention has the advantage that by combining the graphene / carbon nanofiber composite material with cotton fiber, not only the comfort and air permeability of the cotton fiber are retained, but also the excellent antibacterial and anti-mite performance of the cotton fiber is improved. The graphene and carbon nanofibers themselves have good antibacterial properties and can effectively inhibit the growth of bacteria and mites, and the addition of the composite material further enhances this effect.
[0047] The propylene glycol solution treatment step used in the preparation process helps to remove unreacted oxidants on the cotton fibers, which is beneficial to enhance the bonding strength between the composite material and the cotton fibers, which means that after multiple washings, the cotton fibers can still maintain good antibacterial and anti-mite effects;
[0048] The oxidation treatment with sodium periodate solution helps to generate active groups on the surface of cotton fibers, providing favorable conditions for the attachment of graphene / carbon nanofiber composites. At the same time, this treatment also has a certain impact on the crystallinity and physical and mechanical properties of cotton fibers. By optimizing the treatment conditions, these influences can be balanced, so that the final antibacterial and anti-mite healthy cotton fibers can be further improved while maintaining their original performance.
[0049] In summary, the present invention has the following beneficial effects:
[0050] 1. The advantage of the present invention is that the Cu-Ag alloy exists in a pomegranate-like structure, which is conducive to increasing the specific surface area of the alloy and improving the surface activity of the material, thereby enhancing its antibacterial and anti-mite properties. Ag and Cu elements are evenly distributed in the alloy, which helps to achieve a wider antibacterial coverage and reduce dead corners.
[0051] 2. The advantage of the present invention is that, Cu and Ag are both elements with excellent antibacterial properties, and their combined use can further enhance the antibacterial effect of the alloy; the pomegranate-shaped structure Cu-Ag alloy is combined with graphene fiber to prepare healthy cotton fiber with excellent antibacterial and anti-mite properties. This fiber is suitable for making various bedding, clothing, medical supplies, etc., to meet people's needs for healthy life.
[0052] 3. The present invention has the advantage that anhydrous ethanol and deionized water are used for multiple washings during the preparation process, which effectively removes impurities and unreacted raw materials and improves the purity of the nanoparticles. At the same time, the nanoparticles are fully dispersed in the deionized water and anhydrous ethanol through ultrasonic dispersion, which avoids agglomeration between the particles and improves the dispersibility of the nanoparticles.
[0053] 4. The advantage of the present invention is that the copper-silver core-shell bimetallic nanoparticles have a stable core-shell structure, which not only combines the excellent properties of copper and silver, such as the electrical conductivity of copper and the antibacterial property of silver, but also enhances the stability and durability of the nanoparticles through the core-shell structure.
[0054] 5. The advantage of the present invention is that the presence of the silver shell makes the copper-silver core-shell bimetallic nanoparticles have excellent antibacterial properties, and silver ions can destroy the cell membrane and DNA of bacteria, thereby effectively inhibiting the growth and reproduction of bacteria. This antibacterial property makes the material have broad application prospects in the fields of medical treatment, hygiene, textiles, etc.
[0055] 6. The advantage of the present invention is that the nano copper particles are firstly fully treated by ultrasonic dispersion and mechanical stirring, thereby ensuring the uniform dispersion of the nano particles and providing a good foundation for the subsequent coating of the silver shell layer.
[0056] 7. The present invention has the advantages that, through the precise control of dilute nitric acid and sodium hydroxide solution, the nano copper particles are effectively pre-treated, the oxides and other impurities on the surface are removed, the purity and surface activity of the nano particles are improved, and the subsequent uniform coating of the silver shell layer is beneficial. In addition, through the alternating use of deionized water and anhydrous ethanol, the excess coating liquid and impurities are effectively removed, thereby ensuring the purity and dispersibility of the nano particles.
[0057] 8. The advantage of the present invention is that by introducing organic molecules such as glacial acetic acid and oleic acid on the surface of the copper antibacterial agent, its surface properties can be improved, thereby enhancing its antibacterial effect; these organic molecules help to increase the release rate of copper ions on the surface or improve their interaction with bacterial cell membranes, thereby more effectively killing or inhibiting the growth of bacteria, which is beneficial to improving the stability of the modified copper antibacterial agent in the environment.
[0058] 9. The advantage of adopting the present invention is that the finishing agent combines the antibacterial properties of nano-TiO2 and Ag, and the antibacterial effect of the modified copper antibacterial agent, forming a multiple antibacterial and anti-mite mechanism; nano-TiO2 can produce a photocatalytic effect under light conditions, decompose organic matter and kill bacteria; Ag ions have a broad-spectrum antibacterial property and can effectively inhibit the growth of various bacteria; and the modified copper antibacterial agent enhances the antibacterial effect by releasing copper ions.
[0059] 10. The present invention has the advantages that, by selecting a suitable dispersion medium (anhydrous ethanol) and a dispersant (OP), and controlling the stirring time and speed, the obtained emulsion is very stable, which indicates that the nanoparticles in the finishing agent are effectively dispersed and stabilized, avoiding the agglomeration and sedimentation of the particles; the raw materials used, such as nano-TiO2, Ag and modified copper antibacterial agents, are all environmentally friendly materials, and the entire preparation process is carried out under relatively mild conditions without generating toxic and harmful substances.
[0060] 11. The present invention has the advantage that by dissolving graphene oxide in DMF, the graphene oxide can be uniformly dispersed in the solvent, which is the basis for preparing high-quality composite materials, helps to avoid agglomeration, and improves the overall performance of the composite materials;
[0061] Among them, adding PAN to the suspension and stirring it vigorously for a period of time can form a stable spinning solution. The stability of this spinning solution can ensure the smooth progress of the subsequent electrospinning process and reduce problems such as wire breakage during the spinning process.
[0062] 12. The advantage of the present invention is that by combining the graphene / carbon nanofiber composite material with cotton fiber, not only the comfort and breathability of the cotton fiber are retained, but also the excellent antibacterial and anti-mite properties of the cotton fiber are promoted. Graphene and carbon nanofibers themselves have good antibacterial properties and can effectively inhibit the growth of bacteria and mites, and the addition of the composite material further enhances this effect.
[0063] 13. The advantage of the present invention is that the propylene glycol solution treatment step used in the preparation process helps to remove the unreacted oxidant on the cotton fiber, which is beneficial to enhance the bonding strength between the composite material and the cotton fiber, which means that after multiple washings, the cotton fiber can still maintain a good antibacterial and anti-mite effect.
[0064] 14. The advantage of the present invention is that the oxidation treatment with sodium periodate solution helps to generate active groups on the surface of cotton fibers, providing favorable conditions for the attachment of graphene / carbon nanofiber composite materials. At the same time, this treatment also has a certain influence on the crystallinity and physical and mechanical properties of cotton fibers. These influences can be balanced by optimizing the treatment conditions, so that the final antibacterial and anti-mite healthy cotton fibers can be further improved on the basis of maintaining the original performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0065] Figure 1 The invention relates to a preparation process of antibacterial and anti-mite healthy cotton fiber based on a composite of copper-silver alloy and graphene fiber. DETAILED DESCRIPTION
[0066] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. Without departing from the spirit and substance of the present invention, modifications or substitutions made to the methods, steps or conditions of the present invention are within the scope of the present invention.
[0067] If not specifically stated, the technical means used in the examples are conventional means known to those skilled in the art. In addition, all the raw materials used in the examples are known commercial products.
[0068] Example 1
[0069] Step (1) Synthesis of pomegranate-like structure Cu-Ag alloy
[0070] At a temperature of 75°C, a soluble copper salt, polyvinyl pyrrolidone and a soluble silver salt are added to a solvent diethylene glycol to obtain a copper salt solution, a polyvinyl pyrrolidone solution and a silver salt solution; the polyvinyl pyrrolidone solution is added dropwise to the copper salt solution, and a reduction reaction is continued for 1 hour at a temperature of 180°C and under stirring conditions to obtain a Cu suspension; the polyvinyl pyrrolidone solution and the silver salt solution are simultaneously added dropwise to the Cu suspension, and a reduction reaction is continued for 1.5 hours at a temperature of 75°C and under stirring conditions to obtain a Cu-Ag suspension; the Cu-Ag suspension is centrifuged, washed and dried in sequence to obtain a pomegranate-shaped structure Cu-Ag alloy;
[0071] Step (2) Preparation of copper-silver core-shell bimetallic nanoparticles
[0072] Pour 1g of the pomegranate-shaped Cu-Ag alloy prepared in step (1), 5g of PVP and 95ml of ethanol into three-necked flask 1, heat to 60°C and stir to dissolve; Pour 15g of ascorbic acid into three-necked flask 2, then pour 455ml of ethanol, heat to 65°C and stir to dissolve; Keep heating and stirring the three-necked flask 1, pour the solution in the three-necked flask 2 into the three-necked flask 1, continue heating and stirring to react for 5min; After the reaction is completed, stop heating and cool to room temperature, add deionized water to break the stability, and centrifuge at 950 The nano-copper particles were centrifuged at 0 r / min for 1 min to settle, the supernatant was discarded, deionized water was added, ultrasonic dispersion was performed, the nano-copper particles were fully washed in deionized water, the supernatant was discarded by centrifugation, the washing was repeated once, anhydrous ethanol was added, ultrasonic dispersion was performed, the nano-copper particles were fully washed in anhydrous ethanol, the supernatant was discarded by centrifugation, the washing was repeated once, and finally the collected nano-particles were placed in a vacuum drying oven and dried at room temperature under a vacuum condition of -1 MPa for 1 h to obtain a copper-silver core-shell bimetallic nano-particle material;
[0073] Step (3) Copper-silver bimetallic core-shell nanoparticle material
[0074] After the copper-silver core-shell bimetallic nanoparticles prepared in step (2) are fully ground and dispersed, 0.2 g of nano-copper particles are weighed and poured into a three-necked flask, and then 15 ml of deionized water is poured into the flask. The three-necked flask is placed in an ultrasonic cleaner to ultrasonically disperse the nano-copper particles at room temperature while mechanically stirring. The ultrasonic dispersion and mechanical stirring are maintained at room temperature, and 25 ml of 0.1 mol / L dilute nitric acid solution is poured into the three-necked flask. After reacting for 25 seconds, 45 ml of 0.02mol / L sodium hydroxide solution, neutralize nitric acid, complete nano copper pretreatment; maintain ultrasonic dispersion and mechanical stirring at room temperature, pour 100ml of solvent, deionized water containing 0.001mol silver nitrate, 0.004mol ammonia water and 1g gelatin coating solution into a three-necked flask, react for 1min, and complete the silver shell coating; after the reaction is completed, take out the solution, use a centrifuge to centrifuge for 1min at 9500r / min to settle the particles, then pour out the supernatant, add deionized water, ultrasonically disperse, make the nano copper particles fully clean in deionized water, then centrifuge and pour out the supernatant, repeat the washing once, add anhydrous ethanol, ultrasonically disperse, make the nano copper particles fully clean in anhydrous ethanol, then centrifuge and pour out the supernatant, place the collected particles in a vacuum drying oven, and dry at room temperature under -1MPa vacuum conditions;
[0075] Step (4) Surface modification of copper antimicrobial agent
[0076] The antibiotic is dissolved, and then di-tert-butyl dicarbonate is added to react under an inert gas atmosphere to obtain a Boc (tert-butyloxycarbonyl) protected antibiotic; the Boc protected antibiotic, N , N-dimethylaminoethyl glycol, TBTU (tetrafluoroborate) and DIPEA (N, N-diisopropylethylamine) were mixed in a molar ratio of 1:2:3:6 and added to the solvent, and stirred for reaction at room temperature for 10 hours to obtain a mixed product; the mixed product was dissolved, and then tert-butyl bromoacetate and a base were added to react at 45°C in an inert gas atmosphere for 0.5 hours to obtain an antibacterial mixture; the mixture was de-tert-butylated in a mixed solvent of dichloromethane and trifluoroacetic acid, and then precipitated and filtered to obtain an antibacterial agent; under the protection of a nitrogen atmosphere, 15g of a copper antibacterial agent, 1mL of glacial acetic acid and 1mL of oleic acid were added to 350mL of anhydrous ethanol solution in sequence, and refluxed at 75°C for 5 hours. After the reaction was completed, it was washed and filtered with anhydrous ethanol and ultrapure water in turn, and freeze-dried for 20 hours to obtain a modified copper antibacterial agent;
[0077] Step (5) Preparation of nano anti-mite and antibacterial finishing agent
[0078] Weigh 15 g of nano-TiO2 powder, 15 g of Ag, 95 ml of dispersant OP, 15 g of citric acid, and add the modified copper antibacterial agent prepared in step (4). The pH value is 1, the stirring time is 25 min, and the stirring speed is 5550 r / min. The obtained emulsion is very stable and only a small amount of precipitation is obtained after standing. Thus, a nano anti-mite antibacterial finishing agent is prepared.
[0079] Step (6) Preparation of graphene / carbon nanofiber composite material
[0080] First, 0.10 g of graphene oxide was dissolved in 15 g of DMF, and the temperature was set to 25 ° C, the power was set to 95 W, and the frequency was set to 40 Hz for 25 min to obtain a dispersed suspension; then 1 g of PAN was added to the above suspension, and the mass content of graphene oxide in the suspension was 1%; the nano anti-mite and antibacterial finishing agent prepared in step (5) was placed in a constant temperature water bath set at 55 ° C, and vigorously stirred for 12 h to finally obtain the required electrospinning solution, and the copper-silver bimetallic core-shell nanoparticle material prepared in step (3) was used to prepare the precursor of the composite fiber membrane, and then placed in a drying oven and pre-oxidized in an air atmosphere to stabilize the composite fiber precursor. Finally, the pre-oxidized composite fiber membrane was placed in a tubular furnace and carbonized in a nitrogen atmosphere. The heating rate of the tubular furnace was 1 ° C / min, and the temperature was raised to 800 ° C, and then kept warm for 5 min; a graphene / carbon nanofiber composite material was obtained;
[0081] Step (7) Preparation of antibacterial and anti-mite healthy cotton fiber
[0082] After the graphene / carbon nanofiber composite material prepared in step (6) is scour-bleached, the prepared cotton fiber is placed in a sodium periodate solution with a concentration of 0.5 g / L, and then oscillated at 35 r / min for 1 hour at 40°C in the absence of light. After the oxidation is completed, the cotton fiber is immersed in a 0.1 mol / L propylene glycol solution for 25 hours to remove the remaining unreacted oxidant, and finally thoroughly washed with distilled water and dried to obtain antibacterial and anti-mite healthy cotton fiber.
[0083] Example 2
[0084] Step (1) Synthesis of pomegranate-like structure Cu-Ag alloy
[0085] At a temperature of 76°C, a soluble copper salt, polyvinyl pyrrolidone and a soluble silver salt are added to a solvent diethylene glycol to obtain a copper salt solution, a polyvinyl pyrrolidone solution and a silver salt solution; the polyvinyl pyrrolidone solution is added dropwise to the copper salt solution, and a reduction reaction is continued for 1 hour at a temperature of 185°C and under stirring conditions to obtain a Cu suspension; the polyvinyl pyrrolidone solution and the silver salt solution are simultaneously added dropwise to the Cu suspension, and a reduction reaction is continued for 1.5 hours at a temperature of 80°C and under stirring conditions to obtain a Cu-Ag suspension; the Cu-Ag suspension is centrifuged, washed and dried in sequence to obtain a pomegranate-shaped structure Cu-Ag alloy;
[0086] Step (2) Preparation of copper-silver core-shell bimetallic nanoparticles
[0087] Pour 1g of the pomegranate-shaped Cu-Ag alloy prepared in step (1), 6g of PVP and 96ml of ethanol into three-necked flask 1, heat to 62°C and stir to dissolve; Pour 16g of ascorbic acid into three-necked flask 2, then pour 460ml of ethanol, heat to 66°C and stir to dissolve; Keep heating and stirring the three-necked flask 1, pour the solution in the three-necked flask 2 into the three-necked flask 1, continue heating and stirring to react for 6 minutes; After the reaction is completed, stop heating and cool to room temperature, add deionized water to break the stability, and use a centrifuge to centrifuge at 960 0r / min for centrifugation to settle the nano copper particles, then pour out the supernatant, add deionized water, ultrasonically disperse, fully wash the nano copper particles in deionized water, centrifuge and pour out the supernatant, repeat the washing twice, add anhydrous ethanol, ultrasonically disperse to fully wash the nano copper particles in anhydrous ethanol, centrifuge and pour out the supernatant, repeat the washing twice, finally place the collected nanoparticles in a vacuum drying oven, dry at room temperature under -1MPa vacuum conditions for 2h, and obtain a copper-silver core-shell bimetallic nanoparticle material;
[0088] Step (3) Copper-silver bimetallic core-shell nanoparticle material
[0089] After the copper-silver core-shell bimetallic nanoparticles prepared in step (2) are fully ground and dispersed, 0.3 g of nano-copper particles are weighed and poured into a three-necked flask, and then 16 ml of deionized water is poured into the flask. The three-necked flask is placed in an ultrasonic cleaner to ultrasonically disperse the nano-copper particles at room temperature while mechanically stirring. The ultrasonic dispersion and mechanical stirring are maintained at room temperature, and 26 ml of 0.2 mol / L dilute nitric acid solution is poured into the three-necked flask. After reacting for 26 seconds, 46 ml of 0.03mol / L sodium hydroxide solution, neutralize nitric acid, complete nano copper pretreatment; maintain ultrasonic dispersion and mechanical stirring at room temperature, pour 96ml of solvent, deionized water containing 0.002mol silver nitrate, 0.005mol ammonia water and 2g gelatin coating solution into a three-necked flask, react for 2min, and complete the silver shell coating; after the reaction is completed, take out the solution, use a centrifuge to centrifuge at 9600r / min for 2min to settle the particles, then pour out the supernatant, add deionized water, ultrasonically disperse, make the nano copper particles fully clean in deionized water, then centrifuge and pour out the supernatant, repeat the washing 4 times, then add anhydrous ethanol, ultrasonically disperse, make the nano copper particles fully clean in anhydrous ethanol, then centrifuge and pour out the supernatant, place the collected particles in a vacuum drying oven, and dry at room temperature under -1MPa vacuum conditions;
[0090] Step (4) Surface modification of copper antimicrobial agent
[0091] The antibiotic is dissolved, and then di-tert-butyl dicarbonate is added to react under an inert gas atmosphere to obtain a Boc (tert-butyloxycarbonyl) protected antibiotic; the Boc protected antibiotic, N,N-dimethylaminoethyl glycol, TBTU (tetrafluoroborate) and DIPEA (N,N-diisopropylethylamine) are mixed in a molar ratio of 1:2:3:6 and added to a solvent, and the mixture is stirred and reacted at room temperature for 12 hours to obtain a mixed product; the mixed product is dissolved, and then tert-butyl bromoacetate and The alkali reacts at 46°C in an inert gas atmosphere for 1.5 hours to obtain an antibacterial mixture; the mixture is subjected to a de-tert-butylation reaction in a mixed solvent of dichloromethane and trifluoroacetic acid, and then precipitated and filtered to obtain an antibacterial agent; under the protection of a nitrogen atmosphere, 16 g of a copper antibacterial agent, 2 mL of glacial acetic acid and 3 mL of oleic acid are sequentially added to 360 mL of anhydrous ethanol solution, and refluxed at 76°C for 7 hours. After the reaction is completed, it is washed and filtered with anhydrous ethanol and ultrapure water in turn, and freeze-dried for 22 hours to obtain a modified copper antibacterial agent;
[0092] Step (5) Preparation of nano anti-mite and antibacterial finishing agent
[0093] Weigh 16 g of nano-TiO2 powder, 16 g of Ag, 96 ml of dispersant OP, 16 g of citric acid, and add the modified copper antibacterial agent prepared in step (4). The pH value is 2. The stirring time is 26 min and the stirring speed is 5560 r / min. The obtained emulsion is very stable and only a small amount of precipitation is obtained after standing. Thus, a nano anti-mite antibacterial finishing agent is prepared.
[0094] Step (6) Preparation of graphene / carbon nanofiber composite material
[0095] First, 0.10 g of graphene oxide was dissolved in 16 g of DMF, and the temperature was set to 27 ° C, the power was set to 96 W, and the frequency was set to 43 Hz for 26 minutes to obtain a dispersed suspension; then 2 g of PAN was added to the above suspension, and the mass content of graphene oxide in the suspension was 2%; the nano anti-mite and antibacterial finishing agent prepared in step (5) was placed in a constant temperature water bath set at 56 ° C, and vigorously stirred for 14 hours to finally obtain the required electrospinning solution, and the copper-silver bimetallic core-shell nanoparticle material prepared in step (3) was used to prepare the precursor of the composite fiber membrane, and then placed in a drying oven and pre-oxidized in an air atmosphere to stabilize the composite fiber precursor. Finally, the pre-oxidized composite fiber membrane was placed in a tubular furnace and carbonized in a nitrogen atmosphere. The heating rate of the tubular furnace was 6 ° C / min, and the temperature was raised to 1000 ° C, and then kept warm for 6 minutes to obtain a graphene / carbon nanofiber composite material;
[0096] Step (7) Preparation of antibacterial and anti-mite healthy cotton fiber
[0097] After the graphene / carbon nanofiber composite material prepared in step (6) is scour-bleached, the prepared cotton fiber is placed in a sodium periodate solution with a concentration of 10 g / L, and then oscillated at 36 r / min for 5 hours at 42°C in the absence of light. After the oxidation is completed, the cotton fiber is immersed in a 0.3 mol / L propylene glycol solution for 26 hours to remove the remaining unreacted oxidant, and finally thoroughly washed with distilled water and dried to obtain antibacterial and anti-mite healthy cotton fiber.
[0098] Example 3
[0099] Step (1) Synthesis of pomegranate-like structure Cu-Ag alloy
[0100] At a temperature of 80°C, a soluble copper salt, polyvinyl pyrrolidone and a soluble silver salt are added to a solvent diethylene glycol to obtain a copper salt solution, a polyvinyl pyrrolidone solution and a silver salt solution; the polyvinyl pyrrolidone solution is added dropwise to the copper salt solution, and a reduction reaction is continued for 2 hours at a temperature of 210°C and under stirring conditions to obtain a Cu suspension; the polyvinyl pyrrolidone solution and the silver salt solution are simultaneously added dropwise to the Cu suspension, and a reduction reaction is continued for 1.5 hours at a temperature of 80°C and under stirring conditions to obtain a Cu-Ag suspension; the Cu-Ag suspension is centrifuged, washed and dried in sequence to obtain a pomegranate-shaped structure Cu-Ag alloy;
[0101] Step (2) Preparation of copper-silver core-shell bimetallic nanoparticles
[0102] Pour 2 g of the pomegranate-shaped Cu-Ag alloy prepared in step (1), 10 g of PVP and 96 ml of ethanol into three-necked flask 1, heat to 61°C and stir to dissolve; Pour 16 g of ascorbic acid into three-necked flask 2, then pour 460 ml of ethanol, heat to 67°C and stir to dissolve; Keep heating and stirring the three-necked flask 1, pour the solution in the three-necked flask 2 into the three-necked flask 1, continue heating and stirring to react for 6 minutes; After the reaction is completed, stop heating and cool to room temperature, add deionized water to break the stability, and use a centrifuge to centrifuge at 970 0r / min for 4min to allow the nano-copper particles to settle, then the supernatant was discarded, deionized water was added, ultrasonic dispersion was performed, the nano-copper particles were fully washed in deionized water, the supernatant was discarded by centrifugation, the washing was repeated twice, anhydrous ethanol was added, ultrasonic dispersion was performed, the nano-copper particles were fully washed in anhydrous ethanol, the supernatant was discarded by centrifugation, the washing was repeated twice, and finally the collected nano-particles were placed in a vacuum drying oven, and dried at room temperature for 2h under a vacuum condition of -1MPa to obtain a copper-silver core-shell bimetallic nano-particle material;
[0103] Step (3) Copper-silver bimetallic core-shell nanoparticle material
[0104] After the copper-silver core-shell bimetallic nanoparticles prepared in step (2) are fully ground and dispersed, 0.3 g of nano-copper particles are weighed and poured into a three-necked flask, and then 16 ml of deionized water is poured into the flask. The three-necked flask is placed in an ultrasonic cleaner to ultrasonically disperse the nano-copper particles at room temperature while mechanically stirring. The ultrasonic dispersion and mechanical stirring are maintained at room temperature, and 27 ml of 0.2 mol / L dilute nitric acid solution is poured into the three-necked flask. After reacting for 27 seconds, 46 ml of 0.03mol / L sodium hydroxide solution, neutralize nitric acid, complete nano copper pretreatment; maintain ultrasonic dispersion and mechanical stirring at room temperature, pour 96ml of solvent, deionized water containing 0.004mol silver nitrate, 0.005mol ammonia water and 2g gelatin coating solution into a three-necked flask, react for 2min, and complete the silver shell coating; after the reaction is completed, take out the solution, use a centrifuge to centrifuge at 9600r / min for 2min to settle the particles, then pour out the supernatant, add deionized water, ultrasonically disperse, make the nano copper particles fully clean in deionized water, then centrifuge and pour out the supernatant, repeat the washing 2 times, add anhydrous ethanol, ultrasonically disperse, make the nano copper particles fully clean in anhydrous ethanol, then centrifuge and pour out the supernatant, place the collected particles in a vacuum drying oven, and dry at room temperature under -1MPa vacuum conditions;
[0105] Step (4) Surface modification of copper antimicrobial agent
[0106] The antibiotic is dissolved, and then di-tert-butyl dicarbonate is added to react under an inert gas atmosphere to obtain a Boc (tert-butyloxycarbonyl) protected antibiotic; the Boc protected antibiotic, N , N-dimethylaminoethyl glycol, TBTU (tetrafluoroborate) and DIPEA (N, N-diisopropylethylamine) were mixed in a molar ratio of 1:2:3:6 and added to the solvent, and stirred for reaction at room temperature for 15 hours to obtain a mixed product; the mixed product was dissolved, and then tert-butyl bromoacetate and a base were added to react at 55°C in an inert gas atmosphere for 1.5 hours to obtain an antibacterial mixture; the mixture was de-tert-butylated in a mixed solvent of dichloromethane and trifluoroacetic acid, and then precipitated and filtered to obtain an antibacterial agent; under the protection of a nitrogen atmosphere, 16g of a copper antibacterial agent, 3mL of glacial acetic acid and 4mL of oleic acid were added to 355mL of anhydrous ethanol solution in sequence, and refluxed at 76°C for 6 hours. After the reaction was completed, it was washed and filtered with anhydrous ethanol and ultrapure water in turn, and freeze-dried for 22 hours to obtain a modified copper antibacterial agent;
[0107] Step (5) Preparation of nano anti-mite and antibacterial finishing agent
[0108] Weigh 16 g of nano-TiO2 powder, 16 g of Ag, 97 ml of dispersant OP, 16 g of citric acid, and 57 g of citric acid. Add the modified copper antibacterial agent prepared in step (4). The pH value is 5. The stirring time is 27 min and the stirring speed is 5550 r / min. The obtained emulsion is very stable and only a small amount of precipitation is obtained after standing. Thus, a nano anti-mite antibacterial finishing agent is prepared.
[0109] Step (6) Preparation of graphene / carbon nanofiber composite material
[0110] First, 0.10 g of graphene oxide was dissolved in 16 g of DMF, and the temperature was set to 28 ° C, the power was set to 97 W, and the frequency was set to 42 Hz for 27 minutes to obtain a dispersed suspension; then 2 g of PAN was added to the above suspension, and the mass content of graphene oxide in the suspension was 2%; the nano anti-mite and antibacterial finishing agent prepared in step (5) was placed in a constant temperature water bath set at 60 ° C, and vigorously stirred for 24 hours to finally obtain the required electrospinning solution, and the copper-silver bimetallic core-shell nanoparticle material prepared in step (3) was used to prepare the precursor of the composite fiber membrane, and then placed in a drying oven and pre-oxidized in an air atmosphere to stabilize the composite fiber precursor. Finally, the pre-oxidized composite fiber membrane was placed in a tubular furnace and carbonized in a nitrogen atmosphere. The heating rate of the tubular furnace was 5 ° C / min, and the temperature was raised to 1100 ° C, and then kept warm for 10 minutes to obtain a graphene / carbon nanofiber composite material;
[0111] Step (7) Preparation of antibacterial and anti-mite healthy cotton fiber
[0112] After the graphene / carbon nanofiber composite material prepared in step (6) is scourged and bleached, the prepared cotton fiber is placed in a sodium periodate solution with a concentration of 30 g / L, and then oscillated at 40 r / min for 5 hours at 45°C in the absence of light. After the oxidation is completed, the cotton fiber is immersed in a 0.4 mol / L propylene glycol solution for 30 hours to remove the remaining unreacted oxidant, and finally thoroughly washed with distilled water and dried to obtain antibacterial and anti-mite healthy cotton fiber.
[0113] Example 4
[0114] Step (1) Synthesis of pomegranate-like structure Cu-Ag alloy
[0115] At a temperature of 85°C, a soluble copper salt, polyvinyl pyrrolidone and a soluble silver salt are added to a solvent diethylene glycol to obtain a copper salt solution, a polyvinyl pyrrolidone solution and a silver salt solution; the polyvinyl pyrrolidone solution is added dropwise to the copper salt solution, and a reduction reaction is continued for 2 hours at a temperature of 220°C and under stirring conditions to obtain a Cu suspension; the polyvinyl pyrrolidone solution and the silver salt solution are simultaneously added dropwise to the Cu suspension, and a reduction reaction is continued for 2 hours at a temperature of 85°C and under stirring conditions to obtain a Cu-Ag suspension; the Cu-Ag suspension is centrifuged, washed and dried in sequence to obtain a pomegranate-shaped structure Cu-Ag alloy;
[0116] Step (2) Preparation of copper-silver core-shell bimetallic nanoparticles
[0117] Pour 5 g of the pomegranate-shaped Cu-Ag alloy prepared in step (1), 11.1 g of PVP and 100 ml of ethanol into three-necked flask 1, heat to 65°C and stir to dissolve; pour 17.6 g of ascorbic acid into three-necked flask 2, then pour 500 ml of ethanol, heat to 65°C and stir to dissolve; keep heating and stirring the three-necked flask 1, pour the solution in the three-necked flask 2 into the three-necked flask 1, continue heating and stirring to react for 10 minutes; after the reaction is completed, stop heating and cool to room temperature, add deionized water to break the stability, and use a centrifuge to centrifuge. Centrifuge at 10000r / min for 5min to settle the nano copper particles, then pour out the supernatant, add deionized water, ultrasonically disperse, fully wash the nano copper particles in deionized water, centrifuge and pour out the supernatant, repeat the washing 3 times, add anhydrous ethanol, ultrasonically disperse to fully wash the nano copper particles in anhydrous ethanol, centrifuge and pour out the supernatant, repeat the washing 3 times, finally place the collected nanoparticles in a vacuum drying oven, dry at room temperature under -1MPa vacuum conditions for 4h to obtain a copper-silver core-shell bimetallic nanoparticle material;
[0118] Step (3) Copper-silver bimetallic core-shell nanoparticle material
[0119] After the copper-silver core-shell bimetallic nanoparticles prepared in step (2) are fully ground and dispersed, 0.32 g of nano-copper particles are weighed and poured into a three-necked flask, and then poured into 20 ml of deionized water. The three-necked flask is placed in an ultrasonic cleaner to ultrasonically disperse the nano-copper particles at room temperature, while mechanically stirring; maintaining ultrasonic dispersion and mechanical stirring at room temperature, pour 30 ml of 0.1 mol / L dilute nitric acid solution into the three-necked flask, react for 30 seconds, and then pour 50 ml 0.02mol / L sodium hydroxide solution, neutralize nitric acid, complete nano copper pretreatment; maintain ultrasonic dispersion and mechanical stirring at room temperature, pour 97ml of solvent, deionized water containing 0.004mol silver nitrate, 0.005mol ammonia water and 1g gelatin coating solution into a three-necked flask, react for 2min, and complete the silver shell coating; after the reaction is completed, take out the solution, use a centrifuge to centrifuge at 10000r / min for 5min to settle the particles, then pour out the supernatant, add deionized water, ultrasonically disperse, make the nano copper particles fully clean in deionized water, then centrifuge and pour out the supernatant, repeat the washing 4 times, then add anhydrous ethanol, ultrasonically disperse, make the nano copper particles fully clean in anhydrous ethanol, then centrifuge and pour out the supernatant, place the collected particles in a vacuum drying oven, and dry at room temperature under -1MPa vacuum conditions;
[0120] Step (4) Surface modification of copper antimicrobial agent
[0121] The antibiotic is dissolved, and then di-tert-butyl dicarbonate is added to react under an inert gas atmosphere to obtain a Boc (tert-butyloxycarbonyl) protected antibiotic; the Boc protected antibiotic, N , N-dimethylaminoethyl glycol, TBTU (tetrafluoroborate) and DIPEA (N, N-diisopropylethylamine) were mixed in a molar ratio of 1:4:5:8 and added to the solvent, and stirred for reaction at room temperature for 15 hours to obtain a mixed product; the mixed product was dissolved, and then tert-butyl bromoacetate and a base were added to react at 55°C in an inert gas atmosphere for 1.5 hours to obtain an antibacterial mixture; the mixture was de-tert-butylated in a mixed solvent of dichloromethane and trifluoroacetic acid, and then precipitated and filtered to obtain an antibacterial agent; under the protection of a nitrogen atmosphere, 20g of a copper antibacterial agent, 1mL of glacial acetic acid and 5mL of oleic acid were added to 400mL of anhydrous ethanol solution in sequence, and refluxed at 80°C for 8 hours. After the reaction was completed, it was washed and filtered with anhydrous ethanol and ultrapure water in turn, and freeze-dried for 26 hours to obtain a modified copper antibacterial agent;
[0122] Step (5) Preparation of nano anti-mite and antibacterial finishing agent
[0123] Weigh 20 g of nano-TiO2 powder and 20 g of Ag as dispersion medium (anhydrous ethanol) to 100 ml, 30 g of dispersant OP, and 60 g of citric acid, add the modified copper antibacterial agent prepared in step (4), pH is 7, stirring time is 30 min, stirring speed is 6000 r / min, the obtained emulsion is very stable and only a small amount of precipitation is obtained after standing, and a nano anti-mite antibacterial finishing agent is prepared;
[0124] Step (6) Preparation of graphene / carbon nanofiber composite material
[0125] First, 0.12 g of graphene oxide was dissolved in 17 g of DMF, and the temperature was set to 30°C, the power was set to 100 W, and the frequency was set to 40 Hz for 30 min to obtain a dispersed suspension; then 2.88 g of PAN was added to the suspension, and the mass content of graphene oxide in the suspension was 4%; the nano anti-mite and antibacterial finishing agent prepared in step (5) was placed in a constant temperature water bath set at 60°C and stirred vigorously for 24 h to finally obtain the required electrospinning solution; the precursor of the composite fiber membrane was prepared by the copper-silver bimetallic core-shell nanoparticle material prepared in step (3), and then placed in a drying oven and pre-oxidized in an air atmosphere to stabilize the composite fiber precursor; finally, the pre-oxidized composite fiber membrane was placed in a tubular furnace and carbonized in a nitrogen atmosphere, and the heating rate of the tubular furnace was 5°C / min, and the temperature was raised to 1100°C, and then kept warm for 10 min; a graphene / carbon nanofiber composite material was obtained;
[0126] Step (7) Preparation of antibacterial and anti-mite healthy cotton fiber
[0127] After the graphene / carbon nanofiber composite material prepared in step (6) is scourged and bleached, the prepared cotton fiber is placed in a sodium periodate solution with a concentration of 2 g / L, and then oscillated at 40 r / min for 2 hours at 40°C in the absence of light. After the oxidation is completed, the cotton fiber is immersed in a 0.1 mol / L propylene glycol solution for 30 hours to remove the remaining unreacted oxidant, and finally thoroughly washed with distilled water and dried to obtain antibacterial and anti-mite healthy cotton fiber.
[0128] Comparative Example 1
[0129] Step (1) Synthesis of pomegranate-like structure Cu-Ag alloy
[0130] At a temperature of 90°C, a soluble copper salt, polyvinyl pyrrolidone and a soluble silver salt are added to a solvent diethylene glycol to obtain a copper salt solution, a polyvinyl pyrrolidone solution and a silver salt solution; the polyvinyl pyrrolidone solution is added dropwise to the copper salt solution, and a reduction reaction is continued for 5 hours at a temperature of 250°C and under stirring conditions to obtain a Cu suspension; the polyvinyl pyrrolidone solution and the silver salt solution are simultaneously added dropwise to the Cu suspension, and a reduction reaction is continued for 5 hours at a temperature of 90°C and under stirring conditions to obtain a Cu-Ag suspension; the Cu-Ag suspension is centrifuged, washed and dried in sequence to obtain a pomegranate-shaped structure Cu-Ag alloy;
[0131] Step (2) Preparation of copper-silver core-shell bimetallic nanoparticles
[0132] Pour 1g of the pomegranate-shaped Cu-Ag alloy prepared in step (1), 20g of PVP and 100ml of ethanol into three-necked flask 1, heat to 75°C and stir to dissolve; Pour 25g of ascorbic acid into three-necked flask 2, then pour 550ml of ethanol, heat to 75°C and stir to dissolve; Keep heating and stirring the three-necked flask 1, pour the solution in the three-necked flask 2 into the three-necked flask 1, continue heating and stirring to react for 15min; After the reaction is completed, stop heating and cool to room temperature, add deionized water to break the stability, and use a centrifuge to centrifuge at 100 00r / min for 6min to allow the nano-copper particles to settle, then the supernatant was discarded, deionized water was added, ultrasonic dispersion was performed, the nano-copper particles were fully washed in deionized water, then centrifuged and the supernatant was poured out, the washing was repeated 4 times, anhydrous ethanol was added, ultrasonic dispersion was performed to allow the nano-copper particles to be fully washed in anhydrous ethanol, then centrifuged and the supernatant was poured out, the washing was repeated 4 times, and finally the collected nano-particles were placed in a vacuum drying oven and dried at room temperature under a vacuum condition of -1MPa for 12h to obtain a copper-silver core-shell bimetallic nano-particle material;
[0133] Step (3) Surface modification of copper antimicrobial agent
[0134] The antibiotic is dissolved, and then di-tert-butyl dicarbonate is added to react under an inert gas atmosphere to obtain a Boc (tert-butyloxycarbonyl) protected antibiotic; the Boc protected antibiotic, N , N-dimethylaminoethyl glycol, TBTU (tetrafluoroborate) and DIPEA (N, N-diisopropylethylamine) were mixed in a molar ratio of 1:2:3:6 and added to a solvent, and stirred for reaction at room temperature for 30 hours to obtain a mixed product; the mixed product was dissolved, and then tert-butyl bromoacetate and a base were added to react at 60°C in an inert gas atmosphere for 2 hours to obtain an antibacterial mixture; the mixture was de-tert-butylated in a mixed solvent of dichloromethane and trifluoroacetic acid, and then precipitated and filtered to obtain an antibacterial agent; under the protection of a nitrogen atmosphere, 25g of a copper antibacterial agent, 6mL of glacial acetic acid and 6mL of oleic acid were added to 450mL of anhydrous ethanol solution in sequence, and refluxed at 100°C for 10 hours. After the reaction was completed, it was washed and filtered with anhydrous ethanol and ultrapure water in turn, and freeze-dried for 30 hours to obtain a modified copper antibacterial agent;
[0135] Step (4) Preparation of nano anti-mite and antibacterial finishing agent
[0136] Weigh 25g of nano-TiO2 powder and 24g of Ag as dispersion medium (anhydrous ethanol) in 100ml, 35g of dispersant OP, and 65g of citric acid, add the modified copper antibacterial agent prepared in step (3), pH is 8, stirring time is 35min, stirring speed is 6000r / min, the obtained emulsion is very stable and only a small amount of precipitation is obtained after standing, and a nano anti-mite antibacterial finishing agent is prepared;
[0137] Step (5) Preparation of graphene / carbon nanofiber composite material
[0138] First, 0.12 g of graphene oxide was dissolved in 20 g of DMF, and the temperature was set to 35 ° C, the power was set to 100 W, and the frequency was set to 50 Hz for 35 minutes to obtain a dispersed suspension; then 5 g of PAN was added to the above suspension, and the mass content of graphene oxide in the suspension was 4%; the nano anti-mite and antibacterial finishing agent prepared in step (4) was placed in a constant temperature water bath set at 65 ° C, and vigorously stirred for 24 hours to finally obtain the required electrospinning solution, and the copper-silver core-shell bimetallic nanoparticles prepared in step (2) were used to prepare the precursor of the composite fiber membrane, and then placed in a drying oven and pre-oxidized in an air atmosphere to stabilize the composite fiber precursor. Finally, the pre-oxidized composite fiber membrane was placed in a tubular furnace and carbonized in a nitrogen atmosphere. The heating rate of the tubular furnace was 5 ° C / min, and the temperature was raised to 1100 ° C, and then kept warm for 10 minutes to obtain a graphene / carbon nanofiber composite material;
[0139] Step (6) Preparation of antibacterial and anti-mite healthy cotton fiber
[0140] After the graphene / carbon nanofiber composite material prepared in step (5) is scour-bleached, the prepared cotton fiber is placed in a sodium periodate solution with a concentration of 30 g / L, and then oscillated at 50 r / min for 6 hours at 45°C in the absence of light. After the oxidation is completed, the cotton fiber is immersed in a 1 mol / L propylene glycol solution for 60 hours to remove the remaining unreacted oxidant, and finally thoroughly washed with distilled water and dried to obtain antibacterial and anti-mite healthy cotton fiber.
[0141] Comparative Example 2
[0142] Step (1) Synthesis of pomegranate-like structure Cu-Ag alloy
[0143] At a temperature of 95°C, a soluble copper salt, polyvinyl pyrrolidone and a soluble silver salt are added to a solvent diethylene glycol to obtain a copper salt solution, a polyvinyl pyrrolidone solution and a silver salt solution; the polyvinyl pyrrolidone solution is added dropwise to the copper salt solution, and a reduction reaction is continued for 10 hours at a temperature of 300°C and under stirring conditions to obtain a Cu suspension; the polyvinyl pyrrolidone solution and the silver salt solution are simultaneously added dropwise to the Cu suspension, and a reduction reaction is continued for 5 hours at a temperature of 95°C and under stirring conditions to obtain a Cu-Ag suspension; the Cu-Ag suspension is centrifuged, washed and dried in sequence to obtain a pomegranate-shaped structure Cu-Ag alloy;
[0144] Step (2) Preparation of copper-silver core-shell bimetallic nanoparticles
[0145] Pour 2g of the pomegranate-shaped Cu-Ag alloy prepared in step (1), 2g of PVP and 120ml of ethanol into three-necked flask 1, heat to 75°C and stir to dissolve; Pour 10g of ascorbic acid into three-necked flask 2, then pour in 200ml of ethanol, heat to 50°C and stir to dissolve; Keep heating and stirring the three-necked flask 1, pour the solution in the three-necked flask 2 into the three-necked flask 1, continue heating and stirring to react for 2min; After the reaction is completed, stop heating and cool to room temperature, add deionized water to break the stability, and centrifuge at 850 0r / min for centrifugation to settle the nano copper particles, then pour out the supernatant, add deionized water, ultrasonically disperse, fully wash the nano copper particles in deionized water, centrifuge and pour out the supernatant, repeat the washing twice, add anhydrous ethanol, ultrasonically disperse to fully wash the nano copper particles in anhydrous ethanol, centrifuge and pour out the supernatant, repeat the washing twice, finally place the collected nanoparticles in a vacuum drying oven, dry at room temperature under -1MPa vacuum conditions for 2h, and obtain a copper-silver core-shell bimetallic nanoparticle material;
[0146] Step (3) Copper-silver bimetallic core-shell nanoparticle material
[0147] After the copper-silver core-shell bimetallic nanoparticles prepared in step (2) are fully ground and dispersed, 0.1 g of nano-copper particles are weighed and poured into a three-necked flask, and then 10 ml of deionized water is poured into the flask. The three-necked flask is placed in an ultrasonic cleaner to ultrasonically disperse the nano-copper particles at room temperature while mechanically stirring. The ultrasonic dispersion and mechanical stirring are maintained at room temperature, and 15 ml of 0.1 mol / L dilute nitric acid solution is poured into the three-necked flask. After reacting for 20 seconds, 35 ml of 0.02mol / L sodium hydroxide solution, neutralize nitric acid, complete nano copper pretreatment; maintain ultrasonic dispersion and mechanical stirring at room temperature, pour 100ml of solvent, deionized water containing 0.008mol silver nitrate, 0.008mol ammonia water and 5g gelatin coating solution into a three-necked flask, react for 30min, and complete the silver shell coating; after the reaction is completed, take out the solution, use a centrifuge to centrifuge at 10000r / min for 2min to settle the particles, then pour out the supernatant, add deionized water, ultrasonically disperse, make the nano copper particles fully clean in deionized water, then centrifuge and pour out the supernatant, repeat the washing 10 times, then add anhydrous ethanol, ultrasonically disperse, make the nano copper particles fully clean in anhydrous ethanol, then centrifuge and pour out the supernatant, place the collected particles in a vacuum drying oven, and dry at room temperature under -1MPa vacuum conditions;
[0148] Step (4) Preparation of graphene / carbon nanofiber composite material
[0149] First, 1.0 g of graphene oxide was dissolved in 20 g of DMF, and the temperature was set to 35 ° C, the power was set to 100 W, and the frequency was set to 45 Hz for 35 minutes to obtain a dispersed suspension; then 4 g of PAN was added to the above suspension, and the mass content of graphene oxide in the suspension was 5%; then the above suspension was placed in a constant temperature water bath pot set at a temperature of 70 ° C, and vigorously stirred for 24 hours to finally obtain the required electrospinning solution, and the copper-silver bimetallic core-shell nanoparticle material prepared in step (3) was used to prepare the precursor of the composite fiber membrane, and then placed in a drying oven and pre-oxidized in an air atmosphere to stabilize the composite fiber precursor. Finally, the pre-oxidized composite fiber membrane was placed in a tubular furnace and carbonized in a nitrogen atmosphere. The heating rate of the tubular furnace was 8 ° C / min, and the temperature was raised to 1200 ° C, and then kept warm for 12 minutes to obtain a graphene / carbon nanofiber composite material;
[0150] Step (5) Preparation of antibacterial and anti-mite healthy cotton fiber
[0151] After the graphene / carbon nanofiber composite material prepared in step (4) is scour-bleached, the prepared cotton fiber is placed in a sodium periodate solution with a concentration of 0.1 g / L, and then oscillated at 15 r / min for 2 hours at 20°C in the absence of light. After the oxidation is completed, the cotton fiber is immersed in a 0.1 mol / L propylene glycol solution for 20 hours to remove the remaining unreacted oxidant, and finally thoroughly washed with distilled water and dried to obtain antibacterial and anti-mite healthy cotton fiber.
[0152] Comparison of detection experiments:
[0153] The antibacterial and anti-mite healthy cotton fibers obtained in Examples 1 to 4 and Comparative Example Products 1 and 2 were tested, and the specific testing methods are as follows:
[0154] Agar diffusion method
[0155] The agar diffusion method uses agar gel as a medium. Through diffusion, antigens and corresponding antibodies in two different places meet to form an antigen-antibody complex. When the concentration ratio of antigen and antibody is appropriate, a visible precipitation line will be formed at the meeting point. Agar mainly plays the role of a grid in the experiment. Its water content is as high as 99%, allowing soluble antigens and antibodies to diffuse freely in it.
[0156] Mite repellency test
[0157] The mite repellency test is a test method to evaluate the repellency of materials or products to mites. This test is very important to ensure that textiles, daily chemical products, bedding, etc. can effectively reduce the breeding of mites during use. Place a sponge with a thickness of 10mm and a side length of about 200mm in a covered container, and inject an appropriate amount of saturated salt water (the height of the water just submerges the sponge); take 7 culture dishes, place one culture dish in the center of the sticky board as the central culture dish, and place the remaining 6 culture dishes evenly in a petal shape around the central culture dish and fix them with transparent tape. Place samples: Place the samples to be tested (test samples) and control samples (control samples) in the 6 outer culture dishes at intervals. The samples to be tested should be evenly, flatly and tightly laid on the bottom of the culture dish. Introduce mites: Place a certain number (such as 2000±200) of surviving mites on the central culture dish. Cultivation observation: Place the sticky plate assembly with mites and samples on the sponge, cover the container, and place it in a constant temperature and humidity incubator, set the appropriate temperature and humidity (such as 25±2℃ and 75±5% relative humidity). After a certain period of cultivation (such as 24 hours), use a dissecting microscope or stereo microscope to observe and record the number of surviving mites in the sample culture dish and the control sample culture dish.
[0158] Tensile strength test
[0159] Tensile strength test is an important method to evaluate the ability of materials to resist damage when subjected to tensile force. The sample size is based on the test standard. The composite material is cut into specimens of specified size, such as 200mm×50mm (or other specified size). During sample processing, ensure that the sample surface is flat and undamaged, and perform necessary pretreatment in accordance with regulations, such as temperature adjustment, humidity balance, etc.
[0160] Table 1 Antibacterial rate
[0161] Example Antibacterial rate% 1 92 2 94 3 95 4 99 Comparative Example 1 86 Comparative Example 2 83
[0162] As can be seen from Table 1, Example 4 is the best and Comparative Example 2 is the worst. Example 4 has the highest antibacterial rate. The surface-modified copper antibacterial agent can extend its service life and maintain the durability of its antibacterial effect by reducing the nonspecific release of copper ions in the environment. Its stability in the environment is conducive to being improved, which is conducive to inhibiting the growth and reproduction of bacteria. When the copper-silver alloy is used for fiber preparation, its antibacterial performance is further enhanced, and it can more effectively fight against a variety of bacteria.
[0163] Table 2 Mite avoidance rate
[0164] Example Mite avoidance rate% 1 85.89 2 88.23 3 90.54 4 98.99 Comparative Example 1 79.52 Comparative Example 2 79.55
[0165] As can be seen from Table 2, Example 4 is the best and Comparative Example 1 is the worst. The use of the composite material of graphene fiber and copper-silver alloy in Example 1 can significantly enhance the anti-mite performance of the material; graphene can catalyze oxidative stress in mites and effectively inhibit the growth and reproduction of mites, while copper-silver alloy has a good inhibitory effect on mites due to its broad-spectrum antibacterial property.
[0166] Table 3 Tensile strength
[0167] Example Tensile strength cN 1 4.5 2 5.2 3 5.4 4 6.2 Comparative Example 1 3.5 Comparative Example 2 3.1
[0168] As can be seen from Table 1, Example 4 is the best and Comparative Example 2 is the worst. In Example 4, Ag is reinforced with Cu matrix in the form of fine fibers by cold deformation. This fiber-reinforced structure helps to improve the tensile strength of the composite material, thereby improving the strength and toughness of the material. In the modification process of cotton fiber, the surface structure of cotton fiber can be changed by oxidation treatment with sodium periodate, increasing its surface roughness and specific surface area, which helps to combine with graphene / carbon nanofiber composite material. The nanoparticles in the finishing agent are also effectively dispersed and stabilized, which is conducive to avoiding the agglomeration and sedimentation of particles. The higher tensile strength means that the composite material can more effectively resist the damage of external tensile force, thereby extending the service life of the product.
[0169] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art can make non-creative modifications to the present embodiment as needed, but they are protected by patent law as long as they are within the scope of the claims of the present invention.
Claims
1. A method for preparing antibacterial and anti-mite healthy cotton fiber based on a composite of copper-silver alloy and graphene fiber, characterized in that: include: Synthesis of pomegranate-shaped structured Cu-Ag alloy, preparation of copper-silver core-shell bimetallic nanoparticles, copper-silver bimetallic core-shell nanoparticle materials, surface modification of copper antibacterial agents, preparation of nano anti-mite and antibacterial finishing agents, preparation of graphene / carbon nanofiber composites, and preparation of antibacterial and anti-mite healthy cotton fibers.
2. The method for preparing the antibacterial and anti-mite healthy cotton fiber based on the composite of copper-silver alloy and graphene fiber according to claim 1, characterized in that: Step (1) Synthesis of pomegranate-like structure Cu-Ag alloy A soluble copper salt, polyvinyl pyrrolidone and a soluble silver salt are added to a solvent diethylene glycol to obtain a copper salt solution, a polyvinyl pyrrolidone solution and a silver salt solution; the polyvinyl pyrrolidone solution is added dropwise to the copper salt solution, and a reduction reaction is continuously performed under stirring to obtain a Cu suspension; the polyvinyl pyrrolidone solution and the silver salt solution are simultaneously added dropwise to the Cu suspension, and a reduction reaction is continuously performed under stirring to obtain a Cu-Ag suspension; the Cu-Ag suspension is centrifuged, washed and dried in sequence to obtain a pomegranate-shaped structure Cu-Ag alloy; Step (2) Preparation of copper-silver core-shell bimetallic nanoparticles The pomegranate-shaped Cu-Ag alloy, PVP (polyvinyl pyrrolidone) and ethanol prepared in step (1) are poured into a three-necked flask 1, and stirred to dissolve after heating; ascorbic acid is poured into a three-necked flask 2, and then ethanol is poured into the three-necked flask, and stirred to dissolve after heating; the three-necked flask 1 is kept heated and stirred, and the solution in the three-necked flask 2 is poured into the three-necked flask 1, and the heating and stirring reaction is continued; after the reaction is completed, the heating is stopped and the temperature is cooled to room temperature, after deionized water is added to break the stability, the solution is centrifuged to make the nano copper particles settle, and the supernatant is poured out, and deionized water is added, ultrasonic dispersion is performed, and the nano copper particles are fully washed in deionized water, and the supernatant is poured out by centrifugation, and the washing is repeated, and anhydrous ethanol is added, ultrasonic dispersion is performed, and the nano copper particles are fully washed in anhydrous ethanol, and the supernatant is poured out by centrifugation, and the washing is repeated, and finally the collected nano particles are placed in a vacuum drying oven, and dried at room temperature under vacuum conditions to obtain a copper-silver core-shell bimetallic nanoparticle material; Step (3) Copper-silver bimetallic core-shell nanoparticle material After the copper-silver core-shell bimetallic nanoparticles prepared in step (2) are fully ground and dispersed, the nano-copper particles are poured into a three-necked flask, and then poured into deionized water. The three-necked flask is placed in an ultrasonic cleaner and ultrasonically dispersed in the nano-copper particles at room temperature, while mechanically stirring. The ultrasonic dispersion and mechanical stirring are maintained at room temperature, and a dilute nitric acid solution is poured into the three-necked flask. After the reaction, a sodium hydroxide solution is poured to neutralize the nitric acid, thereby completing the pretreatment of the nano-copper. The ultrasonic dispersion and mechanical stirring are maintained at room temperature, and a solvent, a solution containing silver nitrate, are poured into the three-necked flask. deionized water, ammonia and gelatin coating solution, and the silver shell coating is completed after the reaction; after the reaction is completed, the solution is taken out, centrifuged to settle the particles, and then the supernatant is poured out, and deionized water is added, ultrasonic dispersion is performed, so that the nano copper particles are fully washed in deionized water, and then centrifuged to pour out the supernatant, and the washing is repeated, and anhydrous ethanol is added, ultrasonic dispersion is performed, so that the nano copper particles are fully washed in anhydrous ethanol, and then centrifuged to pour out the supernatant, and the collected particles are placed in a vacuum drying oven and dried at room temperature under vacuum conditions; Step (4) Surface modification of copper antimicrobial agent The antibacterial drug is dissolved, and then di-tert-butyl dicarbonate is added to react under an inert gas atmosphere to obtain a Boc (tert-butyloxycarbonyl) protected antibacterial drug; the Boc protected antibacterial drug, N, N-dimethylaminoethyl glycol, TBTU (tetrafluoroborate) and DIPEA (N, N-diisopropylethylamine) are mixed and added to a solvent, and stirred to react at room temperature to obtain a mixed product; the mixed product is dissolved, and then tert-butyl bromoacetate and a base are added to react under an inert gas atmosphere at a certain temperature to obtain an antibacterial mixture; the mixture is subjected to a de-tert-butyl esterification reaction in a mixed solvent of dichloromethane and trifluoroacetic acid, and then precipitated and filtered to obtain an antibacterial agent; under the protection of a nitrogen atmosphere, glacial acetic acid and oleic acid are sequentially added to an anhydrous ethanol solution, and after the reflux reaction is completed, the solution is washed and filtered with anhydrous ethanol and ultrapure water in sequence, and freeze-dried to obtain a modified copper antibacterial agent; Step (5) Preparation of nano anti-mite and antibacterial finishing agent Weigh nano-TiO2 powder, Ag dispersion medium (anhydrous ethanol), dispersant OP, citric acid, and the modified copper antibacterial agent prepared in step (4), and stir. The obtained emulsion is very stable and only a small amount of precipitation is left after standing. A nano anti-mite antibacterial finishing agent is prepared. Step (6) Preparation of graphene / carbon nanofiber composite material First, graphene oxide is dissolved in DMF (N,N-dimethylformamide), the temperature is set to a certain value, the frequency is adjusted for a period of time, and a dispersed suspension is obtained; then PAN is added to the above suspension, the mass content of graphene oxide in the suspension is a certain value, the nano anti-mite and antibacterial finishing agent prepared in step (5) is added, and the above suspension is placed in a constant temperature water bath with a temperature set to a certain value, and vigorously stirred to finally obtain the required electrospinning solution, and the copper-silver bimetallic core-shell nanoparticle material prepared in step (3) is added to prepare the precursor of the composite fiber membrane, and then placed in a drying oven, and pre-oxidized in an air atmosphere to stabilize the composite fiber precursor, and finally the pre-oxidized composite fiber membrane is placed in a tubular furnace and carbonized in a nitrogen atmosphere, and the tubular furnace is heated and then kept warm; Obtaining a graphene / carbon nanofiber composite material; Step (7) Preparation of antibacterial and anti-mite healthy cotton fiber After the graphene / carbon nanofiber composite material prepared in step (6) is scour-bleached, the prepared cotton fiber is placed in a sodium periodate solution and then oscillated in the absence of light. After the oxidation is completed, the cotton fiber is immersed in a propylene glycol solution to remove the remaining unreacted oxidant. Finally, the cotton fiber is thoroughly washed with distilled water and dried to obtain an antibacterial and anti-mite healthy cotton fiber.
3. The method for preparing the antibacterial and anti-mite healthy cotton fiber based on the composite of copper-silver alloy and graphene fiber according to claim 2, characterized in that: Step (1) Synthesis of pomegranate-like structure Cu-Ag alloy At a temperature of 75-85°C, soluble copper salt, polyvinyl pyrrolidone and soluble silver salt are added to a solvent diethylene glycol to obtain a copper salt solution, a polyvinyl pyrrolidone solution and a silver salt solution; the polyvinyl pyrrolidone solution is added dropwise to the copper salt solution, and a reduction reaction is continued for 1-2 hours at a temperature of 180-220°C and under stirring conditions to obtain a Cu suspension; the polyvinyl pyrrolidone solution and the silver salt solution are simultaneously added dropwise to the Cu suspension, and a reduction reaction is continued for 1.5-2 hours at a temperature of 75-85°C and under stirring conditions to obtain a Cu-Ag suspension; the Cu-Ag suspension is centrifuged, washed and dried in sequence to obtain a pomegranate-shaped structure Cu-Ag alloy.
4. The method for preparing the antibacterial and anti-mite healthy cotton fiber based on the composite of copper-silver alloy and graphene fiber according to claim 3, characterized in that: Step (2) Preparation of copper-silver core-shell bimetallic nanoparticles Pour 1-5g of the pomegranate-shaped Cu-Ag alloy prepared in step (1), 5-12g of PVP and 95-100ml of ethanol into three-necked flask 1, heat to 60-65°C and stir to dissolve; Pour 15-20g of ascorbic acid into three-necked flask 2, then pour 455-500ml of ethanol, heat to 65-70°C and stir to dissolve; Keep heating and stirring the three-necked flask 1, pour the solution in the three-necked flask 2 into the three-necked flask 1, continue heating and stirring to react for 5-10min; After the reaction is completed, stop heating and cool to room temperature, add deionized water to break the stability, and centrifuge Centrifuge at 9500-10000r / min for 1-5min to allow the nano-copper particles to settle, then pour out the supernatant, add deionized water, ultrasonically disperse, fully wash the nano-copper particles in deionized water, centrifuge and pour out the supernatant, repeat the washing 1-3 times, add anhydrous ethanol, ultrasonically disperse to fully wash the nano-copper particles in anhydrous ethanol, centrifuge and pour out the supernatant, repeat the washing 1-3 times, finally place the collected nanoparticles in a vacuum drying oven, dry at room temperature under -1-1MPa vacuum conditions for 1-4h to obtain a copper-silver core-shell bimetallic nanoparticle material.
5. The method for preparing the antibacterial and anti-mite healthy cotton fiber based on the composite of copper-silver alloy and graphene fiber according to claim 4, characterized in that: Step (3) Copper-silver bimetallic core-shell nanoparticle material After the copper-silver core-shell bimetallic nanoparticles prepared in step (2) are fully ground and dispersed, 0.2-0.5 g of nano-copper particles are weighed and poured into a three-necked flask, and then 15-20 ml of deionized water is poured into the flask. The three-necked flask is placed in an ultrasonic cleaner to ultrasonically disperse the nano-copper particles at room temperature, while mechanically stirring; while maintaining the ultrasonic dispersion and mechanical stirring at room temperature, 25-30 ml of 0.1-0.5 mol / L dilute nitric acid solution is poured into the three-necked flask, reacted for 25-30 seconds, and then 45-50 ml of 0.02-0.05mol / L sodium hydroxide solution is used to neutralize nitric acid to complete the pretreatment of nano copper; ultrasonic dispersion and mechanical stirring are maintained at room temperature, and 95-100ml of solvent, deionized water containing 0.001-0.005mol silver nitrate, 0.004-0.008mol ammonia water and 1-2g of gelatin coating solution are poured into a three-necked flask, and the reaction is carried out for 1-5min to complete the silver shell coating; after the reaction is completed, the solution is taken out and centrifuged at 9500 Centrifuge at -10000r / min for 1-5min to allow the particles to settle, then pour out the supernatant, add deionized water, and disperse by ultrasound to fully wash the nano-copper particles in deionized water, then centrifuge and pour out the supernatant, repeat the washing 1-4 times, add anhydrous ethanol, and disperse by ultrasound to fully wash the nano-copper particles in anhydrous ethanol, then centrifuge and pour out the supernatant, place the collected particles in a vacuum drying oven, and dry at room temperature under a vacuum condition of -1-1MPa.
6. The method for preparing the antibacterial and anti-mite healthy cotton fiber based on the composite of copper-silver alloy and graphene fiber according to claim 2, characterized in that: Step (4) Surface modification of copper antimicrobial agent The antibiotic is dissolved, and then di-tert-butyl dicarbonate is added to react under an inert gas atmosphere to obtain a Boc (tert-butyloxycarbonyl) protected antibiotic; the Boc protected antibiotic, N,N-dimethylaminoethyl glycol, TBTU (tetrafluoroborate) and DIPEA (N,N-diisopropylethylamine) are mixed in a molar ratio of 1-2:2-4:3-5:6-8 and added to a solvent, and the mixture is stirred for reaction at room temperature for 10-15 hours to obtain a mixed product; the mixed product is dissolved, and then tert-butyl bromoacetate and a base are added at 45-55°C. , react for 0.5-1.5h under an inert gas atmosphere to obtain an antibacterial mixture; carry out de-tert-butyl esterification reaction of the mixture in a mixed solvent of dichloromethane and trifluoroacetic acid, and then precipitate and filter to obtain an antibacterial agent; under the protection of a nitrogen atmosphere, 15-20g of a copper antibacterial agent, 1-5mL of glacial acetic acid and 1-5mL of oleic acid are successively added to 350-400mL of anhydrous ethanol solution, and refluxed at 75-80°C for 5-8h. After the reaction is completed, it is washed and filtered with anhydrous ethanol and ultrapure water in turn, and freeze-dried for 20-26h to obtain a modified copper antibacterial agent.
7. The method for preparing the antibacterial and anti-mite healthy cotton fiber based on the composite of copper-silver alloy and graphene fiber according to claim 6, characterized in that: Step (5) Preparation of nano anti-mite and antibacterial finishing agent Weigh 15-20 g of nano-TiO2 powder, 15-20 g of Ag, 95-100 ml of dispersant (anhydrous ethanol), 15-30 g of dispersant OP (polyoxyethylene octylphenol ether), and 55-60 g of citric acid. Add the modified copper antibacterial agent prepared in step (4), pH 1-7, stirring time 25-30 min, stirring speed 5550-6000 r / min. The obtained emulsion is very stable and only a small amount of precipitation is obtained after standing, thereby preparing a nano anti-mite antibacterial finishing agent.
8. The method for preparing the antibacterial and anti-mite healthy cotton fiber based on the composite of copper-silver alloy and graphene fiber according to claim 7, characterized in that: Step (6) Preparation of graphene / carbon nanofiber composite material First, 0-0.12g of graphene oxide is dissolved in 15-17g of DMF, and the temperature is set to 25-30°C, the power is set to 95-100W, and the frequency is set to 40-45Hz for 25-30min to obtain a dispersed suspension; then 1-3g of PAN is added to the above suspension, and the mass content of graphene oxide in the suspension is 0-4%; the nano anti-mite and antibacterial finishing agent prepared in step (5) is placed in a constant temperature water bath set at 55-60°C and stirred vigorously. 12-24h, finally obtaining the required electrospinning solution, preparing the precursor of the composite fiber membrane by the copper-silver bimetallic core-shell nanoparticle material prepared in step (3), and then placing it in a drying oven, and performing a pre-oxidation treatment in an air atmosphere to stabilize the composite fiber precursor, and finally placing the pre-oxidized composite fiber membrane in a tubular furnace for carbonization treatment in a nitrogen atmosphere, the tubular furnace heating rate is 1-5°C / min, the temperature is raised to 800-1100°C, and then kept warm for 5-10min; obtaining a graphene / carbon nanofiber composite material.
9. The method for preparing the antibacterial and anti-mite healthy cotton fiber based on the composite of copper-silver alloy and graphene fiber according to claim 8, characterized in that: Step (7) Preparation of antibacterial and anti-mite healthy cotton fiber After the graphene / carbon nanofiber composite material prepared in step (6) is scourged and bleached, the prepared cotton fiber is placed in a sodium periodate solution with a concentration of 0.5-30 g / L, and then oscillated at 35-40 r / min for 1-5 hours at 40-45°C in the absence of light. After the oxidation is completed, the cotton fiber is immersed in a 0.1-0.4 mol / L propylene glycol solution for 25-30 hours to remove the remaining unreacted oxidant, and finally thoroughly washed with distilled water and dried to obtain antibacterial and anti-mite healthy cotton fiber.
Citation Information
Patent Citations
Preparing method for titanium-dioxide composite nanometer antibacterial material and product thereof
CN106577750A
Long-acting antibacterial warm-keeping underwear and preparation method thereof
CN106579573A
Antibacterial and mite-proof far infrared health care cellulose fiber and preparation method and application thereof
CN108978190A
Cotton-graphene anti-mite antibacterial bedding fabric and making technology thereof
CN109825926A
Graphene-quaternary ammonium salt long-acting antibacterial mite-inhibiting bed fabric and preparation method thereof
CN114351277A
Cited By
Preparation method of antibacterial anti-mite cool-feeling cotton fiber based on compounding of copper-tungsten alloy and graphene fiber as well as product and application of antibacterial anti-mite cool-feeling cotton fiber
CN119913628A
Composite material based on copper-zinc alloy fibers and alginate fibers and preparation method thereof
CN119932763A
Preparation method of in-situ Ag NWs fiber reinforced Cu-Ag alloy wire
CN120715220A
Porous high-dispersion Ag / Cu / Cu2O composite material for enhancing antibacterial property of microbial exopolysaccharide (EPS) and application of porous high-dispersion Ag / Cu / Cu2O composite material to food packaging
CN120814538A
Silver-copper bimetal electric heating layer coupling solar interface evaporation system and preparation method and application of silver-copper bimetal electric heating layer coupling solar interface evaporation system
CN121342130A
